2013
DOI: 10.4184/asj.2013.7.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Model of Induced Leakage of Polymethylmethacrilate Inside Epidural Space and Prevertebral Muscles During Vertebroplasty in Pigs: Clinical, Macroscopical, and Histological Study

Abstract: Study DesignExperimental study in animals.PurposeStudy the clinical behavior of animals after an induced leakage of cement during vertebroplasty in pigs. Study the distribution of polymethylmetacrilate inside the epidural space and prevertebral muscle. Study the histological findings of the spinal cord and muscles, which contact with cement.Overview of LiteratureAlthough vertebroplasty has a low rate of complication, leakage of cement is highly frequent. There is paucity, in how cement is distributed inside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This finding is characteristic of interfaces between tissues and mobile implants. 21 In our previous study, 15 we found similar results, and we concluded then that the laminar distribution summed to the pulsed compression effect by the dural sac could have avoided the focal accumulation of cement so that there was not enough volume to compress the spinal cord. In 2011, the temperatures of bone cement in the spine canal were measured after vertebroplasty with cement inside the vertebral body and leaking into the canal.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This finding is characteristic of interfaces between tissues and mobile implants. 21 In our previous study, 15 we found similar results, and we concluded then that the laminar distribution summed to the pulsed compression effect by the dural sac could have avoided the focal accumulation of cement so that there was not enough volume to compress the spinal cord. In 2011, the temperatures of bone cement in the spine canal were measured after vertebroplasty with cement inside the vertebral body and leaking into the canal.…”
Section: Discussionsupporting
confidence: 76%
“…We based our technique on a previously published model of epidural and prevertebral leakage of polymethylmethacrylate for vertebroplasty in pigs. 14,15…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-steroidal anti-infl ammatory drugs (NSAIDs) (5), calcium channel blockers (6), pegaptanid sodium (7), mitomycin-C (2), hemostatic polysaccharide agents have been administered (8). All-trans retinoic acid (9), human amniotic fl uid-sodium hyaluranate (10), poly (D, L-lactic acid-co-glycolic acid)-b-poly (ethylene glycol)-b-poly (D, L-lactic acid-co-glycolic acid) thermogel (11), etarnacept (12), dekorin (13), CMC/PO (14), licofelone (15), temozolamide (16), polymethylmethacrylate (17) and hyperbaric oxygen (18) are examples of other agents that have been studied in the treatment of spinal EF.…”
Section: Introductionmentioning
confidence: 99%